Od velemest in mest do nemških urbanih omrežij - Mueller, Bernhard (Urbani izziv, 2000)
For many decades of the 20th century particular cities and towns were understood as international urban systems. For many years the theory on central places and hierarchy of central places, first developed by Loesch, hada decisive influence on spatial research and regional development policies with guiding principles for urbanisation and the development of settlement patterns. However it is becoming ever more evident, that the planned effects of concepts for harmonising intra- and inter-regional differences were not reached. Moreover, inter-regional competition between neighbouring municipalities, as well as modern life styles and residential choices have caused the emergence of new settlement structures with dispersed spatial patterns and string functional ties. It is also true, that urban networking isn't an easy task and that it inherently carries numerous obstacles.
Keywords: Germany; mesta; Nemčija; prostorski razvoj; regionalni razvoj; sodelovanje; suburbanizacija; urbani razvoj; urbanizacija